1997
DOI: 10.1093/nar/25.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilia B: database of point mutations and short additions and deletions, 7th edition

Abstract: The seventh edition of the haemophilia B database lists in easily accessible form all known factor IX mutations due to small changes (base substitutions and short additions and/or deletions of <30 bp) identified in haemophilia B patients. The 1535 patient entries are ordered by the nucleotide number of their mutation. Where known, details are given on: factor IX activity, factor IX antigen in circulation, presence of inhibitor and origin of mutation. References to published mutations are given and the laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…There were two identical donor splice mutations at the first base of intron 6 that were distinct mutations as one was a de novo occurrence, being absent in his maternal grandmother's DNA. A recurrent Arg 29 to Stop mutation in a CpG dinucleotide sequence was associated with a different haplotype from one previously described in the Seattle series (pin 431; Giannelli et al, 1997). Of these, only the referred plasma from the patient with the complex deletion/insertion had detectable factor IX antigen (low level) although this could have been due to residual factor IX concentrate after a recent infusion.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…There were two identical donor splice mutations at the first base of intron 6 that were distinct mutations as one was a de novo occurrence, being absent in his maternal grandmother's DNA. A recurrent Arg 29 to Stop mutation in a CpG dinucleotide sequence was associated with a different haplotype from one previously described in the Seattle series (pin 431; Giannelli et al, 1997). Of these, only the referred plasma from the patient with the complex deletion/insertion had detectable factor IX antigen (low level) although this could have been due to residual factor IX concentrate after a recent infusion.…”
Section: Resultsmentioning
confidence: 68%
“…For haplotypes, the last four mutations were also linked to a BamHI þ allele. For the Thr 397 mutation, factor IX antigen levels vary from 27% to 160% among 24 reported cases (Giannelli et al, 1997); thus the range seen in the current series probably reflects undefined traits that affect factor IX levels, accounting for a 3-fold 'normal range'. * Eleven families reported (unpublished) in 7th edition database with pin numbers (Giannelli et al, 1997) (Furie et al, 1982).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The requirement for cleavage of the propeptide of the F.IX is critical for functional activity. 51 Although the enzyme responsible for the proteolytic cleavage is not identified with certainty, a candidate enzyme, PACE/Furin, can process the pro-FIX precursor when F.IX is overexpressed in a CHO cell system. 52 The level of expression of PACE/Furin in skeletal muscle is unknown, but within the limits of F.IX expression in this study (range, 200-300 ng/mL per 24 hours), no abnormality was found in propeptide cleavage based on N-terminal sequence analysis of purified myotube-synthesized F.IX.…”
Section: Discussionmentioning
confidence: 99%
“…Haemophilia B is an X-linked recessive bleeding disorder caused by mutations in the clotting factor IX gene (Giannelli et al, 1997). A number of the mutations elicit their effect through disruption of the binding, by various transcription factors, to their recognition elements in the factor IX promoter.…”
mentioning
confidence: 99%